Validity and Reliability of Persian Version of LIFE Habits Assessment for Children with Cerebral Palsy Aged between 5 and 13 Years Old - Seyyedeh Narjes Mortazavi; Mehdi Rezaei; Mehdi Rassafiani; Mehdi Tabatabaei; Navid Mirzakhani (University of Social Welfare and Rehabilitation Sciences, 2014)
Objective: The aim of this study is to determine validity and reliability of Persian version of Life Habits questionnaire (LIFE-H) in children 5-13 year old with cerebral palsy (CP) . LIFE-H is a tool for measuring participation in children with disabilities . Materials & Methods: In this study which is a tool making and validation instrument 101 caregivers of children with CP aged 5-13, completed the LIFE-H and a demographic questionnaire. Then the discriminant validity of the items was calculated by using Spearman's test. To evaluate test-retest, 22 of participants completed the questionnaire for the second time with a two weeks interval. Also, face validity of the questionnaire was done in two stages by professionals and caregivers of children, and content validity was verified by Lawshe's method with 13 occupational therapists. Results: Most people have reported good face validity of the questionnaire. Content validity of the Persian version of LIFE-H achieved (except for two items), acceptable score . All items correlate in average to appropriate levels with its own subscale (r> 0.39). Also, all subscales showed a higher correlation with total scores (r >0/50) . I CC values ​​ for all subscales were obtained more than 0.6 and for the questionnaire was 0.78. Conclusion : Results showed that the Persian version of the LIFE_H in the children with cerebral palsy has good validity and reliability. Therefore, it is appropriate assessment to measure participation of children for both research studies and clinical evaluations.